Biocompatible peptide-based hydrogels as nanocarriers for a new antitumoral drug - Hortelão, Ana C. L. (2014)
In this work, several new hydrogelators were developed, containing a Naproxen or a Naphthalene group. The ability of these hydrogels to act as nanocarriers for an antitumoral drug was investigated.